Estimation of water use efficiency (WUE) for efficient irrigation level of oil palm during the main nursery phase - Iput Pradiko; Rana Farrasati; Nuzul Hijri Darlan; Sumaryanto Sumaryanto; Dhaffa Agung Thirafi (Universitas Sebelas Maret, 2025)
The water requirement of oil palm depends on the growth phase (e.g., higher demand during vegetative expansion), environmental conditions (e.g., increased under high vapour pressure deficit), and agricultural practices (e.g., reduced demand through effective water management). Therefore, the water used for oil palm nurseries should be used efficiently to preserve environmental sustainability. The main objective of this research was to determine the water use efficiency (WUE) of oil palm during the main nursery phase. The study evaluated several irrigation strategies inside and outside the greenhouse, including fixed daily watering (two liters per seedling), irrigation based on actual evapotranspiration (ETa), rainfall-dependent watering, and no irrigation. In the outdoor treatments, one group of seedlings was irrigated according to ETa, but watering was withheld when daily rainfall exceeded five mm, while another group received two liters per day only when rainfall was below five mm. These two treatments showed the highest daily evapotranspiration rates, greater vegetative growth, and higher biomass accumulation compared to the other treatments. Notably, the ETa-based treatment was recorded as having the highest water use efficiency (WUE). This study concludes that water loss during evapotranspiration is the main determining factor for irrigation volume. Therefore, irrigation in oil palm nurseries should be based on ETa to improve efficiency and lower costs. These findings offer practical guidance for farmers or plantation management to support more sustainable and cost-effective irrigation practices.